The role of N6-methyladenosine modification in tumor angiogenesis - Qin, Lifei; Zeng, Xinya; Qiu, Xinze; Chen, Xingmei; Liu, Shiquan (Frontiers in Oncology, 2024)
Tumor angiogenesis is a characteristics of malignant cancer progression that facilitates cancer cell growth, diffusion and metastasis, and has an indispensable role in cancer development. N6-methyladenosine (m6A) is among the most prevalent internal modifications in eukaryotic RNAs, and has considerable influence on RNA metabolism, including its transcription, splicing, localization, translation, recognition, and degradation. The m6A modification is generated by m6A methyltransferases (“writers”), removed by m6A demethylases (“erasers”), and recognized by m6A-binding proteins (“readers”). There is accumulating evidence that abnormal m6A modification is involved in the pathogenesis of multiple diseases, including cancers, and promotes cancer occurrence, development, and progression through its considerable impact on oncoprotein expression. Furthermore, increasing studies have demonstrated that m6A modification can influence angiogenesis in cancers through multiple pathways to regulate malignant processes. In this review, we elaborate the role of m6A modification in tumor angiogenesis-related molecules and pathways in detail, providing insights into the interactions between m6A and tumor angiogenesis. Moreover, we describe how targeting m6A modification in combination with anti-angiogenesis drugs is expected to be a promising anti-tumor treatment strategy, with potential value for addressing the challenge of drug resistance.